Analysis of the trends of creatine kinase levels during the preseason of a professional soccer team - Barbosa Coelho, D.; Figueiredo Morandi, R.; Melo, M. A.; Leao Andrade, R.; Coelho da Paixao, R.; Silami-Garcia, E. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
Physical exercises can result in tissue damage on the muscular system, including during the preseason, which is a period of physical training aiming subsequent competitions. The aim of this study was to analyze the behavior of plasma CK as a marker of muscle damage during preseason of a professional soccer team; determine when preseason CK levels reach their peak value; and verify CK concentration on preceding moment to the first official match of the season. Professional soccer players (n = 31) attended this study (24.3 ± 3.9 years, 181.0 ± 7.0 cm, 9.1 ± 1.3%GC and 66.0 ± 4.5 mLO2/kg/min). The plasma concentration of CK was determined at the beginning of the preseason (M1), 4 (M2), 10 (M3) and 15 (M4) days after. We identified CK values of 178.2 ± 12.0, 540.0 ± 59.1, 389.8 ± 49.5, 408.7 ± 45.0 U/L for M1, M2, M3 and M4 respectively. The peak concentration of CK occurred on M2 (p<0.05). The analysis of the behavior of plasma CK revealed increased levels throughout the preseason of a professional soccer team compared to the holiday period. The peak value of CK was reached on the 4th day of preseason. The concentration of CK on the day prior to the first official match of the season proved to be in the range of values recommended for professional players.